Analysis of the Use of School Operational Assitance Funds at SMP Negeri 19 Takengon - Islamudin Islamudin; Alfi Syahrin; Iskandar Iskandar (Universitas Muhammadiyah Enrekang, 2024)
This research aims to describe the analysis of the use of school operational assistance funds. This research uses a descriptive approach, descriptive research is research that is intended to investigate the conditions, circumstances or other things that have been mentioned, the results of which are presented in the form of a research report. The preparation of this research uses a qualitative descriptive method which is carried out by collecting data, digesting information and formulating information, then analyzing and concluding to determine the suitability of the management of School Operational Assistance. The research results show that (1) The system and procedures for the use of School Operational Assistance (BOS) funds carried out at SMP Negeri 19 Takengon have met good procedures. (2) The person responsible for all activities using School Operational Assistance (BOS) funds is the principal. Where the use is carried out by the school treasurer who must be attached in accordance with accounting principles. (3) Overall control of the implementation of operational activities has been in accordance with the regulations and procedures set by the Ministry of Education, where the implementation of the use of School Operational Assistance (BOS) activities has achieved the target and is effective, timely and free from deviations.